Coronary Vascular Disease: A General Review with Specific Reference to Etiology - Gyanendra Gupta; Gagan Devi (International Journal of Biomedical Innovations and Engineering, 2024)
Cardiovascular disease (CVD), the foremost cause of mortality worldwide, has surged by 60% globally, reaching 20.5 million deaths in 2021 from 12.1 million in 1990, as per the latest report from the World Health Federation. While this increase is alarming on a global scale, it raises even greater concerns in countries like India where heart ailments are afflicting individuals at a younger age. The escalation of CVD among the younger population in this region is particularly worrisome. The factors driving this trend are diverse, with diabetes, obesity, smoking, and alcohol consumption emerging as major contributors to the early onset of heart disease. These lifestyle choices and health conditions not only increase the risk of cardiovascular issues but also worsen their impact. Tackling this growing problem requires a comprehensive approach, starting with raising public awareness about the root causes of cardiovascular diseases. By implementing targeted educational programs, public health campaigns, and community outreach efforts, we can foster a culture that prioritizes proactive heart health management. These initiatives play a vital role in raising awareness about cardiovascular risks and equipping individuals with the knowledge needed to make healthier lifestyle choices. Providing people with the tools and resources to address these risks empowers them to take control of their health, adopt preventive measures, and make informed decisions about their well-being. Such efforts are crucial not only in reducing the prevalence of premature deaths caused by heart disease but also in laying the foundation for a healthier society. By promoting sustained heart health awareness and encouraging a shift toward healthier habits, we can ensure a brighter, healthier future for the coming generations.
Keywords: Cardiovascular disease; Diabetes; Obesity and Aetiology; World Health Federation